Risk factors for a kyphosis recurrence after short-segment temporary posterior fixation for thoracolumbar burst fractures. (August 2019) - Aono, Hiroyuki; Ishii, Keisuke; Takenaka, Shota; Tobimatsu, Hidekazu; Nagamoto, Yukitaka; Horii, Chiaki; Yamashita, Tomoya; Furuya, Masayuki; Iwasaki, Motoki
Highlights: We investigated rick factor for kyphosis after temporary fixation for burst fracture. Fractured vertebrae were well reduced and maintained after surgery. Kyphosis recurrence was observed at disc level mainly after implant removal. Preoperative kyphotic deformity and canal compromise ratio were the risk factors. Abstract: Short-segment temporary posterior spinal instrumentation has been widely used to treat thoracolumbar burst fractures. However, kyphosis recurrence without hardware failure has become a concern. Therefore, we investigated risk factors for kyphosis recurrence after short-segment temporary fixation for thoracolumbar burst fractures. Our prospective multicenter study involved 76 consecutive patients with thoracolumbar burst fractures who underwent short-segment temporary posterior fixation using ligamentotaxis with Schanz screws and without fusion. Patients were divided into two groups -kyphosis recurrence and no kyphosis recurrence- according to correction loss of the kyphotic angle. Clinical and radiographic data were examined to reveal the risk factors for postoperative kyphosis recurrence. After surgery, all patients experienced fracture union. Kyphotic deformity was reduced significantly, and maintenance of the reduced vertebra was successful. However, mean 9.1° loss of correction in kyphotic angle was observed. Statistical analysis revealed that a high ratio of canal compromise before surgery, as seen on computed tomography scanning, and a large preoperative kyphotic angle influenced kyphosis recurrence. In conclusion, short-segment temporary posterior fixation yields satisfactory results regarding reduction and maintenance of fractured vertebrae. However, correction loss after implant removal is associated with a high compromised canal ratio before surgery and a large preoperative kyphotic angle.